PENGARUH LEVEL BATU BATA DENGAN LAMA PEMERAMAN TERHADAP PENYUSUTAN BOBOT DAN ORGANOLEPTIK TELUR ASIN ITIK - Amin, Atep Syahrul; Nurhayatin, Titin; Herawati, Ervi; Rohayati, Tati (Fakultas Pertanian Universitas Garut, 2025)
Eggs are a perishable livestock product. Therefore, eggs are often preserved by processing them into salted eggs. The purpose of this study was to determine the effect of brick level with curing duration which had the best effect on weight loss and organoleptic salted duck eggs. This research was conducted in February 2023 in Kampung Cikendi Rt/Rw 001/004 Sukawangi Village, Tarogong Kaler District, Garut Regency. This study used the RAL method with 6 treatments and 3 replications until there is 18 experimental units. The treatment in this study were: P1 = 2 parts of bricks: 1 part of salt with 7 days curing, P2 = 2 parts of bricks : 1 part of salt with 14 days of curing, P3 = 2.5 parts of bricks : 1 part of salt with curing 7 days, P4 = 2.5 parts of brick : 1 part of salt with 14 days of curing, P5 = 3 parts of brick : 1 part of salt with 7 days of curing, P6 = 3 parts of stone : 1 part of salt with 14 days of curing. The variables observed in this study were: weight loss, color, aroma, taste. The results salted duck eggs showed that brick level with curing time had an effect on weight loss and organoleptic salted duck eggs. Brick level a ratio of 2.5 parts of brick : 1 part of salt and curing time of 14 days gave the best effect.